Splenic Hamartomas in Alagille Syndrome: Case Report and Literature Review. (1st August 2014) - James, Aaron W; Nguyen, Alan; Said, Jonathan; Genshaft, Scott; Lassman, Charles R; Teitell, Michael
<x xml:space="preserve">Abstract</x> Alagille syndrome is a rare autosomal dominant disorder with characteristic findings of paucity of intrahepatic bile ducts, congenital heart disease, and vertebral, ocular, and renal abnormalities. We present a unique autopsy case of an 18-year-old female with Alagille syndrome and splenic hamartomas. Autopsy findings included growth restriction, Tetralogy of Fallot, paucity of intrahepatic bile ducts, end-stage renal disease with mesangiolipidosis, and splenomegaly with two well-circumscribed, splenic tumors. Histologic findings of the splenic tumors revealed disorganized vascular channels lined by cells without cytologic atypia. Immunohistochemical analysis demonstrated CD8+CD31+ endothelial cells, consistent with splenic hamartomas. In summary, Alagille syndrome is a rare genetic disorder characterized by JAG1 mutations and disrupted Notch signaling. Review of the literature highlights the importance of Notch signaling in vascular development and disorders. However, to our knowledge this is the first description of splenic hamartomas in Alagille syndrome.